Review of the genus Crisicoccus Ferris (Hemiptera: Coccomorpha: Pseudococcidae) in Japan with description of a new species, and the identity of a South Korean mealybug misidentified as Crisicoccus matsumotoi (Shiraiwa 1935) - Tanaka, Hirotaka; Kamitani, Satoshi (Zootaxa, 2022)
Mealybug species found in Japan belonging to the genus Crisicoccus Ferris (Hemiptera: Coccomorpha: Pseudococcidae) are reviewed and the adult female of each valid species is described or update described and illustrated. Crisicoccus seruratus (Kanda 1933) and C. matsumotoi (Shiraiwa 1935) are found to be the same species, and are synonymized. A neotype is designated for C. seruratus for the purpose of taxonomic stability. A species from Japan previously identified by Ezzat & McConnell (1956) as C. matsumotoi is found to differ from specimens of C. matsumotoi from Japan and is described as a new species, Crisicoccus ezzati sp. nov. Other Crisicoccus species recorded from Japan (C. azaleae (Tinsley 1898) and C. pini (Kuwana 1902)) are characterized based on recently collected specimens. A species in South Korea that was misidentified as C. matsumotoi for over 40 years is identified as Spilococcus pacificus (Borchsenius 1949) and an updated description and an illustration of the adult female are provided. Identification keys to relevant genera and to adult females of species of Crisicoccus in Japan and Spilococcus Ferris in South Korea are provided.